ESTIMATION OF HYPERTENSION RISK FROM LIFESTYLE FACTORS IN COASTAL POPULATIONS - Zata Ismah; Tri Bayu Purnama; Reinpal Falefi; Luthfiah Mawar; Cindy Lestari; Citra Cahyati Nst (Jurnal Riset Kesehatan, 2021)
The prevalence of hypertension in coastal areas was still high between 2007 and 2018 with the highest prevalence in 2007 at 53.3%. The purpose of this research was to analyze the prediction of hypertension based on the determinants of the lifestyle of the coastal population. The type of this research is using cross-sectional research design, with a total sample of 210 people in the coastal area of Medan Belawan. The data were collected using an instrument in the form of a questionnaire, body mass index measurement using a manual weight balance and a stature meter and blood pressure using an sphygmomanometer aneroid. The selection of candidates as predictive variables is carried out by chi-square test analysis, followed by multivariate analysis using binary logistic regression test and the formulation model to find predictions hypertension, namely age ≥ 45 years has a 3.040 times greater risk of suffering from hypertension than age 45 years (p = 0.001; 95% CI = 1.549-5.966) and obesity nutritional status has a large 2.284 times greater risk of suffering from hypertension than nutritional status was not obese (p = 0.028; 95% CI = 1.091-4.780). The results of the calculation of the probability from the modeling, it is found that if a person is ≥ 45 years old and has a nutritional status of obesity, the probability of suffering hypertension is 99.99%.